Reinvestigation of Phryganella paradoxa (Arcellinida, Amoebozoa) Penard 1902. (8th July 2018) - Dumack, Kenneth; Kahlich, Christopher; Lahr, Daniel J. G.; Bonkowski, Michael
Abstract: A major drawback in testate amoeba research is a general lack of scientific studies combining molecular approaches and classical laboratory experiments. We isolated five yet uncultured testate amoebae of the genus Phryganella Penard, 1902 from three different rivers and one pond in Germany. Based on established cultures we show their morphology, which we studied by light and electron microscopy, and present their unique feeding mode on abundant and common pennate diatoms like Nitzschia spp. and Synedra spp., whose frustules are bent and frequently, but not always, broken during the feeding process. We further obtained the first SSU rDNA sequences of strains of the family Phryganellidae, all of which contain introns. We used the sequences to confirm the taxonomic placement of the Phryganellidae in the Arcellinida (Amoebozoa), branching as a sister group to the Cryptodifflugiidae.